Phylogeography and differentiation of white-nest swiftlet (Aerodramus fuciphagus) in Malaysia - Goh, Wei Lim (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The edible birds'-nest builder, white-nest swiftlet (Aerodramus fuciphagus), has received much attention in Malaysia over past few decades. It has become one of the important natural resources in Malaysia and contributed to the profitable birds'-nest industry. Due to the great market demand, wild populations of white-nest swiftlet are declining. In recent years, swiftlet farming becomes a new trend in edible bird nests industry in Malaysia and also in the Southeast Asia. Phylogeographic study of the white-nest swiftlet populations could provide the information of the white-nest swiftlet subspecies identification, recent gene flow among the white-nest swiftlet populations and the recent population expansion. Thus, this study is aimed to: (a) resolve the dispute over the classification within species; and (b) investigate the patterns and structure of the relationships among the populations in Peninsular Malaysia, Sarawak and Sumatra, in which the resulted information will be useful in the strategy planning for white-nest swiftlet conservation and for the swiftlet farming. In this study, six populations had been studied. They are middle Baram, Sibu, Sitiawan, Selangor, Kuantan, Endau-Rompin and Sumatra. Based on phylogenetic analyses of the 558 bp of the mitochondrial cytochrome b and 462 bp of the control region, there are two major clades with a deep divergence among all the white-nest swiftlet populations studied. Clade II is closely related to the Aerodramus fuciphagus vestitus while Clade I is closely related to A. f germani. The grouping of different clades is inconsistent with the geographical distribution. However, Clade II is not participated by the individual from the east coast of Malaysia, while Clade I is not participated by the individual from middle Baram. The statistical analyses supported the phylogenetic analyses. The results suggest that there is no substantial gene flow among the populations in Clade I, Clade II and `Garman Cluster'. The possible Pleistocene refugia were suggested based on the test of population expansion. Further investigation by using longer DNA sequence and involving larger sample size is needed to confirm whether the Clade I and Clade II could be classified into different subspecies. Both cytochrome b and control region have shown their potential in the phylogeographic study of the white-nest swiftlet.